Effect of Quality of Work Life on Work Motivation and Job Satisfaction and Their Impact on Turnover Intention on Outsource Employees - Najib Zamzami; Dewi Susita; Siti Nurjanah (Profesional Muda Cendekia Publishing, 2022)
This study aims to analyze the effect of Quality of Work Life on Work Motivation and Job Satisfaction and its Impact on Turnover Intention of Outsource Employees in Area 4 PT. Kereta Commuter Indonesia. The population in this study were all outsource employees in Area 4 at the PT. Kereta Commuter Indonesia in Jakarta with a total sample of 195 respondents. The analytical method used in this research is using Structural Equation Modeling (SEM). The results of this study indicate that there is a significant positive effect between the Quality of Work Life on Work Motivation in outsource area 4 employees at PT. Kereta Commuter Indonesia, there is a significant positive effect between the Quality of Work Life on Job Satisfaction in outsource area 4 employees at PT. Kereta Commuter Indonesia, there is a significant negative effect between Quality of Work Life on Turnover Intention in outsource area 4 employees at PT. Kereta Commuter Indonesia, there is a significant negative effect between Work Motivation on Turnover Intention on outsource area 4 employees at PT. Kereta Commuter Indonesia, there is a significant negative effect between Job Satisfaction on Turnover Intention in outsource area 4 employees at PT. Kereta Commuter Indonesia, there is an indirect influence between Quality of Work Life on Turnover Intention through Work Motivation on outsource employees area 4 at PT. Kereta Commuter Indonesia, and there is an indirect effect between Quality of Work Life on Turnover Intention through Job Satisfaction on outsource employees area 4 at PT. Kereta Commuter Indonesia